The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ans.15925
|View full text |Cite
|
Sign up to set email alerts
|

Handheld, accelerometer‐based navigation versus conventional instrumentation in total knee arthroplasty: a meta‐analysis

Abstract: Background: Precise and accurate alignments in total knee arthroplasty are important predictors for survivorship and functional outcomes. We aim to compare accelerometer-based navigation (ABN) to conventional instrumentation (CONV), patient-specific instrumentation (PSI) and computer-assisted surgery (CAS) in published literature. Methods: A systematic search of publications from databases (MEDLINE, EMBASE and Cochrane) was obtained from inception to 15 August 2018. A random-effects meta-analysis was used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…They concluded that larger samples and longer follow‐up periods are required to support the trend of better patient outcomes using CAS in TKA. A recent meta‐analysis by Shihab et al concluded neither individual studies nor pooled mean differences found PAD was statistically superior in improving any patient‐reported outcome variable (Knee Society Score, Oxford Knee Score and SF‐36) with at least 6‐month follow‐up 5 …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…They concluded that larger samples and longer follow‐up periods are required to support the trend of better patient outcomes using CAS in TKA. A recent meta‐analysis by Shihab et al concluded neither individual studies nor pooled mean differences found PAD was statistically superior in improving any patient‐reported outcome variable (Knee Society Score, Oxford Knee Score and SF‐36) with at least 6‐month follow‐up 5 …”
Section: Discussionmentioning
confidence: 98%
“…A marginal, but non‐statistically significant, improvement in the coronal and sagittal prosthetic alignment was found in the PAD group. Other studies have demonstrated high rates of precision using PAD in restoration of individual component and overall lower limb alignment 1–5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature search showed no specific cut off values of rotational mal-alignment prediction revision rates and till date one study by Gharaibeh et al 10 has compared the difference in FCR and found an insignificant reduction in the outliers in the ABN group compared to the conventional group. 32 As the femoral component rotation in ABN is set by conventional methods we searched studies that have compared component rotations obtained in conventional technique with that of the CAS 33,34 and Patient specific instrumentation (PSI) 35 . They reported significantly better rotational placement obtained with the CAS but the data regarding the failure of TKA with respect to rotational mal-alignment in these cohorts have not been reported.…”
Section: Discussionmentioning
confidence: 99%